Nueva tecnología de brocas PDC optimiza la tasa de penetración en la Cuenca del Valle Medio del Magdalena, Colombia (2021)
Cleaning hydraulics can significantly affect the performance of a polycrystalline diamond bit, the volume of the cuttings, the type of formation and the design limitations in the bit can cause inefficient cuttings evacuation compromising the bottom cleaning, resulting in a lower performance in penetration rate.